CDK4/6 inhibitors versus PI3K/AKT/mTOR inhibitors in women with hormone receptor-positive, HER2-negative metastatic breast cancer: An updated systematic review and network meta-analysis of 28 randomized controlled trials - Xu, Hangcheng; Wang, Yan; Han, Yiqun; Wu, Yun; Wang, Jiayu; Xu, Binghe (Frontiers in Oncology, 2022)
Background Updated evidence was required to compare the efficacy and safety of cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) inhibitors for patients with hormone receptor-positive and HER2-negative metastatic breast cancer. Methods A systematic review and network meta-analysis was conducted utilizing data from randomized controlled trials (RCTs) that contained interventions of CDK4/6 inhibitors or PI3K/AKT/mTOR inhibitors. Progression-free survival (PFS), overall survival (OS), and treatment-related adverse events (TRAEs) were primary outcomes of interest. Pooled hazard ratios (HRs) and odds ratios (ORs) with 95% credible intervals (CrIs) were used to assess the survival outcomes and safety profiles, respectively. Results A total of 28 RCTs with 12,129 participants were included. Pooled analysis showed that CDK4/6 inhibitors significantly prolonged PFS than PI3K/AKT/mTOR inhibitors (HR, 0.81; 95% CrI, 0.69–0.94), whereas no significant differences were detected regarding OS. After balancing the treatment lines and metastatic sites, the superiority of CDK4/6 inhibitors only appeared in the visceral and non-visceral subgroups. Among CDK4/6 inhibitors, abemaciclib was significantly better than others in ≥3 grade neutropenia (OR, 0.04; 95% CrI, 0.01–0.15). The incidence of stomatitis and digestive disorders was different among diverse kinds of PI3K/AKT/mTOR inhibitors. Discrepancies appeared regarding TRAEs of hepatotoxicity, diarrhea, and hyperglycemia among different interventions. Conclusions CDK4/6 inhibitors showed better efficacy in PFS, but the benefits disappeared when taking treatment line into consideration. Specific and discrepant safety profiles were found in two categories of agents. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022321172.